Analysis of the effectiveness of WhatsApp in improving online learning English - Deddy Supriady (Universitas Lampung, 2020)
This research was a quantitative study using a questionnaire instrument. This study aimed to determine the responses of students of SMP Negeri in Bandar Lampung in the learning process using the WhatsApp application and to analyzed its effectiveness from the results of the questionnaire. Students involved in this study amounted to 30 students. Students were asked to fill out a questionnaire that has been made by the researcher, which amounts to 20 statements. dx.doi.org/10.23960/aksara/v21i2.pp185-190